2011
DOI: 10.1002/anie.201102165
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Synthesis of Sequence‐Defined T‐, i‐, and U‐Shape Polymers for pDNA and siRNA Delivery

Abstract: Artificial oligo(ethylene amino) acids, together with selected natural amino acids and fatty acid modifications, have been used for the solid‐phase‐assisted synthesis of polymers with precise sequence, topology, and modifications (see picture). First proof‐of‐concept studies demonstrate the high potential of such polymers in pDNA and siRNA delivery. K=lysine, A=alanine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
224
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 174 publications
(227 citation statements)
references
References 29 publications
2
224
1
Order By: Relevance
“…The preserved silencing activity of the conjugated siRNA was first shown in comparison to unmodified siRNA in a standard setting, transfecting Neuro2A/ eGFPLuc cells (Figure 3d and Figure S10) using the defined but untargeted polycationic carrier 46. 27 Results reveal that the silencing efficiency as well as cytotoxicity is not negatively affected by the attachment of the endosomolytic peptide via a disulfide linkage. Efficient and Specific Reporter Gene Silencing in Vitro.…”
Section: Articlementioning
confidence: 90%
See 1 more Smart Citation
“…The preserved silencing activity of the conjugated siRNA was first shown in comparison to unmodified siRNA in a standard setting, transfecting Neuro2A/ eGFPLuc cells (Figure 3d and Figure S10) using the defined but untargeted polycationic carrier 46. 27 Results reveal that the silencing efficiency as well as cytotoxicity is not negatively affected by the attachment of the endosomolytic peptide via a disulfide linkage. Efficient and Specific Reporter Gene Silencing in Vitro.…”
Section: Articlementioning
confidence: 90%
“…Schaffert et al already showed that Stp-bearing structures bind nucleic acids very efficiently when crosslinked via disulfide bonds. 27 Thus cysteines were incorporated to enhance polyplex stability. The stabilizing effect is shown in a gel shift assay (Figure 3a), comparing the functional oligomer 356 with the analogue 420, bearing serines instead of cysteines.…”
Section: Articlementioning
confidence: 99%
“…Studies of lipid and polymer carriers have implicated at least two common elements: chemical groups to bind small RNAs and nanoparticle (NP)-stabilizing hydrophobicity, which combine to encapsulate RNA molecules inside stable NPs and release small RNAs into the cytosol after endocytosis (35). Particular tertiary amines with optimal pK a , alkyl chains, and defined topology/ structure have been identified in effective carriers (2)(3)(4)(5)(6)(7)(8)(9)(10)(35)(36)(37).…”
mentioning
confidence: 99%
“…44 To verify the nontoxic properties also in case of protein delivery, a cell viability test was performed. This confirmed this assumption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Transfection oligomer 386 was synthesized as previously reported. 44 SPDP modified proteins (1 mg) were diluted in Hepps buffer (1 mL, 0.5 M, pH 8.5) and 2-fold molar excess of oligomer 386 (compared to covalently bound linker), which was predissolved in water (50 mg/mL), was added for the modification of nlsEGFP. For the modification of β-galactosidase, a 5-fold molar excess of oligomer 386 (compared to covalently bound linker), which was predissolved in water (50 mg/mL), was used.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%